2016
DOI: 10.1155/2016/9848263
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-11 Modulates Inflammation and AttenuatesToxoplasma gondiiPathogenesis

Abstract: Toxoplasma gondii is an obligate intracellular parasite that is the etiologic agent responsible for toxoplasmosis. Infection with T. gondii results in activation of nucleotide binding domain and leucine rich repeat containing receptors (NLRs). NLR activation leads to inflammasome formation, the activation of caspase-1, and the subsequent cleavage of IL-1β and IL-18. Recently, a noncanonical inflammasome has been characterized which functions through caspase-11 and appears to augment many biological functions p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
18
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 49 publications
3
18
0
1
Order By: Relevance
“…Casp1 −/− Casp11 −/− mice are also susceptible to infection by the protozoa Toxoplasma gondii and Trypanosoma cruzi, a phenotype associated with reduced IL-1β or IL-18 production [161][162][163]. A further study demonstrates that in response to infection with T. gondii, mice lacking caspase-11 alone have reduced levels of local and systemic cytokines during the acute phase, whereas inflammation is elevated in the brain during the chronic phase of infection 164. Further investigations are required to unveil individual functions of inflammatory caspases in protozoan infections.MouseProtozoan Phenotype compared to wildtype mice Casp1 −/− Casp11 −/− Leishmania amazonensis…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…Casp1 −/− Casp11 −/− mice are also susceptible to infection by the protozoa Toxoplasma gondii and Trypanosoma cruzi, a phenotype associated with reduced IL-1β or IL-18 production [161][162][163]. A further study demonstrates that in response to infection with T. gondii, mice lacking caspase-11 alone have reduced levels of local and systemic cytokines during the acute phase, whereas inflammation is elevated in the brain during the chronic phase of infection 164. Further investigations are required to unveil individual functions of inflammatory caspases in protozoan infections.MouseProtozoan Phenotype compared to wildtype mice Casp1 −/− Casp11 −/− Leishmania amazonensis…”
mentioning
confidence: 91%
“…A further study demonstrates that in response to infection with T. gondii , mice lacking caspase-11 alone have reduced levels of local and systemic cytokines during the acute phase, whereas inflammation is elevated in the brain during the chronic phase of infection (164). Further investigations are required to unveil individual functions of inflammatory caspases in protozoan infections.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, our research has recently revealed that caspase-11 modulates Inflammation during Toxoplasma gondii infection. 78 Using Casp11 -/- mice, our results revealed that noncanonical Inflammasome signaling significantly impacts neuro-Inflammation and cyst burden during the chronic phases of disease. 78 While the mechanism underlying these findings remains unclear, these data suggest a role of caspase-11 in the sensing and response to a currently unidentified molecular pattern associated with this eukaryotic parasite or imply that noncanonical Inflammasome signaling is functioning in response to intracellular changes driven by the parasite.…”
Section: Nlr Inflammasomesmentioning
confidence: 83%
“…78 While the mechanism underlying these findings remains unclear, these data suggest a role of caspase-11 in the sensing and response to a currently unidentified molecular pattern associated with this eukaryotic parasite or imply that noncanonical Inflammasome signaling is functioning in response to intracellular changes driven by the parasite. 78 Thus, it is highly likely that future studies will continue to expand the role of noncanonical Inflammasome function and signaling.…”
Section: Nlr Inflammasomesmentioning
confidence: 96%
“…In sum, these studies suggest roles for IL-1 β , IL18, IL-1R, NLRP1 and/or NLPR3 inflammasome sensors, the inflammasome adaptor protein ASC, and inflammatory caspases-1 and −11. 2528 However, the role of IL-1 signaling in the brain during chronic infection has not been addressed.…”
Section: Introductionmentioning
confidence: 99%